2015
DOI: 10.5469/neuroint.2015.10.2.60
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Flow Diverter Treatment of Intracranial Aneurysms Related to the Fetal-type Posterior Communicating Artery

Abstract: PurposeThe pipeline embolization device (PED) is a flow diverter that has shown promise in the treatment of intracranial aneurysms. Close to one-fifth of aneurysms, however, fail to occlude after PED placement. This study aims to identify anatomical features and clinicopathologic factors that may predispose failed aneurysm occlusion with the PED.Materials and MethodsWe retrospectively reviewed all anterior circulation unruptured saccular aneurysms treated with the PED in a single-center. The primary outcome me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 16 publications
1
31
1
Order By: Relevance
“…They found that the female gender had a higher rate of aneurysm occlusion, but failed to show any statistically significant association between other factors and the result of the PED treatment. 13 Aneurysms originating from the PCOM itself rather than the ICA at the origin of PCOM, may not have sufficient pipeline coverage of the aneurysm neck, which could explain the failed obliteration in these studies. Anatomical characteristics of aneurysms and branching artery are as important as flow or demand theory in terms of obliteration success rate with PED.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…They found that the female gender had a higher rate of aneurysm occlusion, but failed to show any statistically significant association between other factors and the result of the PED treatment. 13 Aneurysms originating from the PCOM itself rather than the ICA at the origin of PCOM, may not have sufficient pipeline coverage of the aneurysm neck, which could explain the failed obliteration in these studies. Anatomical characteristics of aneurysms and branching artery are as important as flow or demand theory in terms of obliteration success rate with PED.…”
Section: Discussionmentioning
confidence: 81%
“…21 Tsang et al reported similar obliteration rates for PCOM aneurysms with fetal PCA. 13 They evaluated the effect of factors such as gender, aneurysm location, size, aspect ratio, neck-width and prior treatment on obliteration rate. They found that the female gender had a higher rate of aneurysm occlusion, but failed to show any statistically significant association between other factors and the result of the PED treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, their review of the previously published literature is incomplete and indeed this phenomenon has been described by our own series of 4 patients several months earlier [2]. Soon, thereafter, it was described by Tsang et al [3], and followed by the recent article by Zanaty et al These publications were likely in development simultaneously, but we wish to point out the previously published literature on the topic and reinforce the phenomenon observed across the 3 series.…”
mentioning
confidence: 50%